The Role of ICT in Enhancing Speaking Skills in Extramural English Context - Zam, Fakhruddin Zam (Universitas Muhammadiyah Prof. DR. HAMKA, 2023)
Information and Communication Technology (ICT) has played a pivotal role in education, particularly in English Language Teaching (ELT), by simplifying students’ learning process and facilitating teachers’ teaching strategies. Numerous ICTs have been utilized and found effective in enhancing speaking skills not just constrained in the confines of the classroom. Thus, this literature review delves into the multifaceted role of ICT in enhancing students’ speaking skills within the unique realm of Extramural English (EE). By synthesizing several relevant studies published within the last 10 years, it navigates through various ICT tools to enhance speaking skills, illuminating the manifold benefits of ICT in EE. The findings underscore the significance of ICT tools such as videoconferencing platforms, Automatic Speech Recognition (ASR), social media, and digital games to enhance students’ speaking skills. The effectiveness of ICT is heightened when integrated into EE activities, which fosters an autonomous learning process, including independent and self-directed learning. Consequently, teachers are highly recommended to provide more opportunities for students to engage in various ICTs in EE. Keywords: ICT, Extramural English, Speaking Skills